Insights From Recent Literature on Economic Development and Empowerment in Indonesia - Berliana Iffada; Fiskia Syafa’ati; Wisnu Mawardi (LifeSciFi, 2023)
This paper examines the economic development challenges and opportunities in Indonesia, focusing on regional disparities, poverty alleviation, and sustainable growth. Through an analysis of various studies, it highlights the importance of addressing issues such as demographic pressures, inadequate infrastructure, financial constraints, and systemic inequalities that hinder development, especially in remote and vulnerable regions. The research emphasizes the need for targeted government intervention, infrastructure investment, and policies that promote inclusive growth and empower marginalized communities. Additionally, the paper explores the role of sustainable innovation, particularly in agriculture, fisheries, and tourism, as a means to drive inclusive economic development. The potential of the green economy and digital technologies is also discussed, with a focus on how these sectors can contribute to environmental sustainability and job creation. The study calls for comprehensive, well-designed policies that align economic development with social welfare and environmental goals, ensuring long-term prosperity for all segments of the population. Overall, the findings suggest that Indonesia’s future economic success depends on strategic efforts to integrate sustainable practices, improve infrastructure, and foster inclusive growth at both the national and local levels.